2021
DOI: 10.3389/fpsyg.2021.663829
|View full text |Cite
|
Sign up to set email alerts
|

Learning Handwriting: Factors Affecting Pen-Movement Fluency in Beginning Writers

Abstract: Skilled handwriting of single letters is associated not only with a neat final product but also with fluent pen-movement, characterized by a smooth pen-tip velocity profile. Our study explored fluency when writing single letters in children who were just beginning to learn to handwrite, and the extent to which this was predicted by the children’s pen-control ability and by their letter knowledge. 176 Norwegian children formed letters by copying and from dictation (i.e., in response to hearing letter sounds). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…Letter knowledge was assessed in terms of letter recognition, 16 and letter naming, [16][17][18] copying familiar letters, as well as unfamiliar symbols. 18 Letter recognition was influenced by handwriting fluency, 12,16,18 and name-writing, 17 in preschool children. Reutzel, et al, 18 found that letter-naming and letter-writing fluency were associated.…”
Section: Letter Knowledge (N = 4)mentioning
confidence: 99%
See 1 more Smart Citation
“…Letter knowledge was assessed in terms of letter recognition, 16 and letter naming, [16][17][18] copying familiar letters, as well as unfamiliar symbols. 18 Letter recognition was influenced by handwriting fluency, 12,16,18 and name-writing, 17 in preschool children. Reutzel, et al, 18 found that letter-naming and letter-writing fluency were associated.…”
Section: Letter Knowledge (N = 4)mentioning
confidence: 99%
“…Therefore, it was concluded that a lack of letter knowledge causes disfluency in handwriting. 16 According to Gerde, et al, 17 the most important predictor of children's name writing was letter knowledge, specifically capital letters.…”
Section: Letter Knowledge (N = 4)mentioning
confidence: 99%
“…Few authors have presented approaches to segmenting brushstrokes [1,2,[14][15][16]. Spatial segmentation approaches have categorized strokes based on spatial features such as local minimum/maximal coordinates or have deconstructed characters into predefined components [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Few authors have presented approaches to segmenting brushstrokes [1,2,[14][15][16]. Spatial segmentation approaches have categorized strokes based on spatial features such as local minimum/maximal coordinates or have deconstructed characters into predefined components [14,16,17]. Fitjar et al [16] predefined the strokes needed to trace letters; for example, the letter "A" was decomposed into three lines (two slanted and one horizontal).…”
Section: Introductionmentioning
confidence: 99%
“…Handwriting involves a complex co-ordination of linguistic, perceptual, cognitive and motor abilities (Weintraub et al, 2009). Research on handwriting is continuing to determine the exact factors underpinning handwriting acquisition (Fitjar et al, 2021) and the most effective methods for supporting children to master this skill (Engel et al, 2018). Current research supports the contribution of occupational therapy handwriting programmes which emphasise gross and fine motor skills, visual-motor-integration and visual perception to handwriting development (Lee, 2022; Tse et al, 2019).…”
Section: Introductionmentioning
confidence: 99%